DESCRIPTION OF THE MANUSCRIPT OF “MAHBUBUL QULUB” - Aziza Xakimova (The Conference Hub, 2025)
This article talks about the study and copies of Alisher Navai's work “Mahbubul Qulub” and the description of the copy stored under inventory number 872 in the fund of manuscript and lithographic literary resources of Tashkent State University of Uzbek Language and Literature named after Alisher Navai.
Keywords: manuscript copies, originality, calligraphy, nastaliq, colophon, title, race, politeness, praise, na't, cause of praise, tahbeh.